Novel Therapeutic Considerations in Bone and Soft Tissue Sarcoma - Szkandera, Joanna; Andreou, Dimosthenis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Sarcomas are a group of rare cancers that arise in connective tissues of the body. Surgical resection is pivotal for the management of locoregional disease. In locally advanced or metastatic disease settings, systemic therapy has an important role in the multidisciplinary management of sarcoma. Cytotoxic therapy has been the primary treatment for many years. However, recent advances in molecular pathogenesis, the investigation of the tumour microenvironment, changes in clinical trial design, and increased international collaboration have led to the development of histology-driven therapy. Furthermore, genomic profiling has highlighted that, while some sarcomas have complex karyotypes, others are driven by translocation, amplification, and mutation, representing targets for the development of novel therapies. Checkpoint inhibitors have been used as single agents or in combination in clinical sarcoma trials. This progress will move the therapeutic modality in sarcoma patients from the "one-size-fits-all" approach towards a more personalized therapeutic algorithm and better outcomes soon. In this Special Issue, we present original research and review articles highlighting novel therapeutic approaches in the treatment of sarcoma patients.